The extent of the contribution of the determinants of organizational support in the enhancement of the mental status of banking services - A study of the views of a sample of employees in a number of banks in the city of Dohuk - حسن, شيماء محمد صالح; جانكير, مها مصطفى (Journal of Economics and Administrative Sciences, 2019)
The objective of this study is to determine the extent to which the determinants of organizational support contributed to enhancing the mental status of banking services in a number of banks in Dohuk governorate in order to diagnose the correlation between the perceived organizational support and the mental status of services. Availability in the environment of banks and to enhance the mental position from the point of view of customers as the main hypotheses focused on the nature of the relationship between the dimensions of research among them has been tested these hypotheses using statistical and descriptive methods have been The study concluded that the contribution of organizational support, which is understood by the bank's management, has clear implications for the development of the level of services provided in the minds of the beneficiaries. The research concluded with a number of proposals, including: To give employees the attention and appreciation they feel for the support provided by the senior management and commensurate with their potentials and work on developing them continuously through providing the environment suitable for work materially and morally.